THE IMPORTANCE OF AUTONOMIC DISORDERS IN THE PATHOGENESIS OF IRRITABLE BOWEL SYNDROME IN MEDICAL WORKERS - Umirova S.M., Bebitova Sh.E. (Central Asian Journal of Medicine, 2025)
This study investigates the prevalence and clinical characteristics of irritable bowel syndrome (IBS) among healthcare workers, a group often exposed to high levels of stress and irregular work schedules. A total of 60 individuals were examined, and IBS symptoms were identified in 83.3% of them. The most common subtype was diarrhea-predominant IBS, followed by mixed and constipation-predominant types. Heart rate variability analysis revealed signs of autonomic nervous system dysfunction in all IBS subtypes, with the most significant imbalances observed in the mixed-type group. The study also found a strong correlation between autonomic imbalance and the severity of IBS symptoms. These findings highlight the importance of addressing psycho-emotional stress and autonomic regulation in the prevention and management of IBS, especially in healthcare professionals.